2019
DOI: 10.1177/1049732319873330
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers’ Anticipatory Grief: A Conceptual Framework for Understanding Its Multiple Challenges

Abstract: The end-of-life trajectory of cancer patients in palliative care (PC) elicits an anticipatory grief (AG) process in family caregivers (FCs). Although widely recognized, AG lacks conceptual clarification. This study aims to qualitatively explore the experience of FCs of patients with terminal cancer to identify the core characteristics and the specific adaptive challenges related to AG in the context of end-of-life caregiving. Data were collected through in-depth semi-structured interviews conducted in a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 48 publications
(49 reference statements)
3
87
0
12
Order By: Relevance
“…4,5,17 However, the importance of aiding parents in their coping with grief prior to their child's death is becoming more evident in research and in theories on loss and grief. 7,18,19 Theories emphasize that bereaved parents have to adjust to a 'new reality' where the child is physically absent. In order to make this transition parents have to cope with several conflicting emotions, to eventually adjust their plans and integrate the loss in their autobiographical memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,17 However, the importance of aiding parents in their coping with grief prior to their child's death is becoming more evident in research and in theories on loss and grief. 7,18,19 Theories emphasize that bereaved parents have to adjust to a 'new reality' where the child is physically absent. In order to make this transition parents have to cope with several conflicting emotions, to eventually adjust their plans and integrate the loss in their autobiographical memory.…”
Section: Discussionmentioning
confidence: 99%
“…In order to make this transition parents have to cope with several conflicting emotions, to eventually adjust their plans and integrate the loss in their autobiographical memory. 4,[20][21][22][23] An important aspect of this adjustment, that characterizes the process of bereavement, are two components of anticipatory grief; 7,24 preparedness and awareness time on the impending death. 25,26 Studies have shown that HCPs are able to positively influence parental preparedness by conducting end-of-life conversations, in which topics such as prognoses, future scenario's, and grief and loss are discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This anticipatory grief has been the focus of much research. Findings from a qualitative study suggest that this type of grief results in traumatic distress from the exposure to a family member’s closeness to death, and the losses resulting from anticipated separation [ 33 ]. These demands can result in intense emotions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Research in AG has since expanded to encompass several social phenomena, albeit there are still only a few intervention studies focused on FCGs of patients with cancer. [ 3 5 6 ] The reason may be a lack of thorough understanding or consensus on the influencing factors of AG, focused on patients' disease-related and demographic factors. [ 7 8 9 10 11 12 13 14 15 ] Disease-related and demographic factors contribute to screening high-risk groups, but it is difficult to plan interventions which are conducive to improve AG.…”
Section: Introductionmentioning
confidence: 99%